ANALYSIS OF THE VALUE-ADDED TAX IMPLEMENTATION AT PT. INTITERA PRIMAYUDHA - Kacaribu, Anton Adventus; Vincent, Eric (IJOSMAS, 2022)
This research aims to analyze the implementation of value-added tax law and regulation in a small to medium-sized company. It is to obtain representative data for the small to medium-sized companies regarding the effectiveness of regulation implementation.The data used in this research are the primary data obtained from the company in the form of tax returns, tax invoices, interviews and warning letters issued by tax officers. This research uses descriptive and qualitative research methods. The calculation for the tax return for each month of the year 2018 until 2020 is already in compliance with the regulation. From 2018 to 2020, there are 28 rectifications, implementation of VAT is not effective due to the amount of rectification. The research shows that value-added tax has an increasing amount of intricacy in its implementation. In addition, the research also shows that the implementation of value-added tax law or regulation in small to medium-sized companies is ineffective and flawed in its practice.